1995
DOI: 10.1093/oxfordjournals.humrep.a136172
|View full text |Cite
|
Sign up to set email alerts
|

Andrology: Results of 55 intracytoplasmic sperm injection cycles in the treatment of male-immunological infertility

Abstract: Antisperm antibodies present in the semen can be a primary cause of infertility. If the proportion of spermatozoa carrying antisperm antibodies is very high, then usually a poor result ensues in standard in-vitro fertilization. We therefore employed intracytoplasmic sperm injection (ICSI) in 55 cycles (37 patients) where the proportion of antisperm antibody-bound spermatozoa was 80% or higher, as determined by the mixed antiglobulin reaction (MAR) test. The type and location of antisperm antibodies were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(46 citation statements)
references
References 0 publications
0
41
1
4
Order By: Relevance
“…In addition, some authors believe that the presence of significant levels of antisperm antibodies is an indication to always perform ICSI, 42,43 despite a recent meta-analysis concluding that there is no benefit of ICSI over IVF in cases of antisperm antibody-mediated male factor infertility. 44 For cryopreserved sperm from cancer patients, no prospective comparative studies pitting the use of IVF versus ICSI are available in the literature.…”
Section: Absolute Indications For Icsi In Male Factor Infertilitymentioning
confidence: 99%
“…In addition, some authors believe that the presence of significant levels of antisperm antibodies is an indication to always perform ICSI, 42,43 despite a recent meta-analysis concluding that there is no benefit of ICSI over IVF in cases of antisperm antibody-mediated male factor infertility. 44 For cryopreserved sperm from cancer patients, no prospective comparative studies pitting the use of IVF versus ICSI are available in the literature.…”
Section: Absolute Indications For Icsi In Male Factor Infertilitymentioning
confidence: 99%
“…42 The pregnancy rates in the former treatments are somewhat diminished, whereas the use of ICSI offers patients success rates as high as those of non-ASAaffected couples undergoing conventional IVF. 43 Unexplained Infertility.…”
Section: Anovulationmentioning
confidence: 99%
“…However, in the most severe cases the Intracytoplasmic Sperm Injection (ICSI) is generally recommended. Indeed, Naggy et al (1995) demonstrated that there was no significant difference of pregnancy rates resulting from ICSI practice with antibody levels above 80% and those with negative ASA tests. However, the number of poor quality embryos was higher among those with ASAs greater than 80% [17].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Naggy et al (1995) demonstrated that there was no significant difference of pregnancy rates resulting from ICSI practice with antibody levels above 80% and those with negative ASA tests. However, the number of poor quality embryos was higher among those with ASAs greater than 80% [17]. If the sperm parameters are normal according to the recommendations of the WHO 2010, the preparation of semen in view IIU is recommended, in case where the parameters are deleterious the therapeutic indication are the IVF and ICSI.…”
Section: Discussionmentioning
confidence: 99%